1997
DOI: 10.1111/j.1745-6592.1997.tb01191.x
|View full text |Cite
|
Sign up to set email alerts
|

Byproduct Formation During the Reduction of TCE by Zero‐Valence Iron and Palladized Iron

Abstract: Trichloroethene (TCE) was reduced with zero‐valence iron and palladized iron in zero‐head‐space extractors. Progress of the reaction in these batch studies was monitored with purge‐and‐trap gas chromatography and a flame ionization detector. When a 5 ppm initial concentration of TCF. reacts with zero‐valence iron, approximately 140 ppb of vinyl chloride persists for as long as 73 days. The concentration of vinyl chloride (approximately If) ppb) remaining with palladized iron is approximately an order of magnit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
50
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 7 publications
5
50
1
Order By: Relevance
“…Reductive dechlorination of chlorinated solvents by iron was first reported by Sweeny (1). Later, Gillham and others proposed exploiting these reactions for in situ remediation of groundwater contaminated by chlorinated solvents (2,3,4,5). Although reaction rates and reaction byproducts of most one and two carbon chlorinated compounds with iron have been measured, little is known about the reaction mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Reductive dechlorination of chlorinated solvents by iron was first reported by Sweeny (1). Later, Gillham and others proposed exploiting these reactions for in situ remediation of groundwater contaminated by chlorinated solvents (2,3,4,5). Although reaction rates and reaction byproducts of most one and two carbon chlorinated compounds with iron have been measured, little is known about the reaction mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Production and accumulation of chlorinated byproducts due to the low reactivity of iron powders towards lightly chlorinated hydrocarbons. For example, reduction of PCE and TCE by zerovalent iron has been observed to produce cis-1,2-DCE and VC [12,13]. Both compounds are of considerable toxicological concern.…”
Section: Introductionmentioning
confidence: 99%
“…As such, degradation rates vary among Fe filings obtained fiom different sources as a result of differences in surface characteristics such as specific surface area; surface chemical composition, and extent of surface oxidation (Gillham and O'Hannesin 1994;Horney et al 1995;Liang et al 1997). Laboratory studies have suggested that single step is unlikely and that stepwise dechlorination must take place on the metal surface (O'Hannesin 1993; Gillham and O'Hannesin 1994;Matheson and Tratnyek 1994;Sivavec and Horney 1995;Liang et al 1995;Pds et al 1995).…”
Section: Dechlorination Of Chlorinated Solvents By Zero-valence Iron mentioning
confidence: 99%
“…In collaboration with the UofA, researchers in the Environmental Sciences Division at O W L found that a bimetallic preparation of Fe with a small amount i complete dechlorination (for example: fiom TCE to ethylene or ethane) in a 3 -2 of palladium (Pd) (nominally 0.05% by weight) was a superior reductant for TCE (Korte et al 1995b(Korte et al , 1997bMuftikian et al 1995;Liang et al 1997;Grittini et al 1996). The bimetallic system yielded dechlorination kinetics that were one to two orders of magnitude faster than those for zero-valence iron alone.…”
Section: Dechlorination Of Chlorinated Solvents By Zero-valence Iron mentioning
confidence: 99%